Dragonfly Molecular Diagnostic Platform: A Rapid Point-of-Care Solution for Monkeypox and Skin Lesion Pathogens - Dr Kenny Cardenas; Dr Matthew Cavuto; Dr Marcus Pond; Dr Ivana Pennisi; Mr Sohail Mirza; Mr Mark Comer; Dr Isobel Stokes; Dr Sian Lant; Dr Rebecca P Sumner; Dr Luca Miglietta; Dr Frankie Bolt; Prof Alison Holmes; et al. (International Journal of Infectious Diseases)
Introduction: The WHO's declaration of a monkeypox (mpox) clade II outbreak as a Public Health Emergency of International Concern in 2022 underscored the global threat posed by this virus. By February 2024, the outbreak had spread to 117 non-endemic countries, resulting in 94,707 reported cases and 181 deaths. Under-detection and misdiagnosis due to atypical presentation drove explosive dissemination, underscoring the urgency for rapid differential point-of-care diagnostic solutions for sensitive routine specimen testing. Methods: To address this need, we adapted the Dragonfly™ Molecular Diagnostic Platform for the differential diagnosis of skin-tropic viruses. Utilising Loop-Mediated Isothermal Amplification (LAMP)-based assays, our platform covers a spectrum of viruses including orthopoxviruses genus (OPXV), mpox (clades I and II), herpes simplex virus type 1 (HSV-1), herpes simplex virus type 2 (HSV-2), and varicella-zoster virus (VZV). The Dragonfly Platform integrates SmartLid™ technology for sample preparation in under 5 minutes, coupled with lyophilized colorimetric LAMP chemistry (LyoLAMP™). A pilot study performed at North West London Pathology, Imperial College Healthcare NHS Trust, analysed 164 clinical samples, including 51 mpox clade II positive cases, to assess Dragonfly's performance compared to gold standard methods like qPCR. Results: Our LAMP-based assays exhibited a limit of detection ranging between 50-500 copies per reaction across all pathogens. The Dragonfly platform demonstrated high sensitivity and specificity, with 96.1% (95%CI) sensitivity and 100% (95%CI) specificity for OPXV, and 94.1% (95%CI) sensitivity and 100 (95%CI) specificity for mpox. Additionally, Dragonfly detected 9 VZV, 18 HSV-1, and 7 HSV-2 cases, all confirmed by qPCR. Discussion: Dragonfly's LAMP-based colorimetric approach offers a sample-to-result diagnostic solution for infectious diseases. Its portability and rapid testing (under 40 minutes) without the need for laboratory infrastructure or cold chain requirements make it a valuable tool for on-site diagnostics. The Dragonfly skin test panel, targeting OPXV, mpox, HSV-1, HSV-2, and VZV, supports the differential diagnosis of skin lesions and aids in screening and surveillance of suspected mpox cases. While LAMP-based solutions for mpox detection have emerged, none provide a fast, low-resource sample-to-result solution like Dragonfly. Conclusion: The recent mpox outbreak underscores the critical need for accessible, rapid, point-of-care diagnostics for screening and surveillance. Dragonfly's sample-to-result solution for skin lesions addresses this need, offering accessible diagnostics in the field and aiding in outbreak control efforts.